The Use of Misoprsotol in Pregnancy - Elhassan M.D, Elhassan M. (Gezira Journal of Health Sciences; Vol 4 No 2 (2008), 2008)
Misoprsotol is a Prostaglandin E1 analogue that had been approved by the Food and Drug Administration (FDA) to be taken orally for the prevention and treatment of gastric ulcers associated with the use of non steroidal anti-inflammatory drugs. It has also become an important drug in obstetrical practice because of its uterotonic and cervical ripening actions. Misoprsotol is useful in the treatment of miscarriage, cervical ripening before surgical evacuation in cases of embryonic death, fetal death and particularly in induction of labour. The drug may also be used to treat and even prevent postpartum hemorrhage. However misoprostol is not approved for any of these indications in the United States of America (USA), the manufacturing country or elsewhere. Current products labeling include a warning that misoprostol is contraindicated during pregnancy because of its abortifacient properties. However the Food and Drug Administration (FDA) recognizes that, in certain circumstances the “off-label” uses of approved drugs are appropriate, rational and accepted medical practice (1) . Prescribing a medication for an off-label indication is common in the treatment of pregnant women and is not considered experimental if based on scientific evidence (2) . The purpose of this article is to review the large body of evidence supporting the use of misoprostol in pregnancy. This includes reviewing pharmacokinetics and physiology, mechanism of action, off-label conflicts, efficacy, dosage variations, different routes of administration and safety of misoprostol in pregnancy and postpartum haemorrhage under pregnancy three trimesters course.